Legal Liability of Shipping Companies in Cash-on-Delivery Transactions for Violations of Consumer Rights - Bella Islamia Mokodompit; Nirwan Junus; Moh. Taufiq Zulfikar Sarson (The Easta Journal Law and Human Rights, 2026)
The development of e-commerce has driven the use of the Cash on Delivery (COD) method as a payment alternative that enhances consumer trust, yet it also raises legal issues regarding the liability of shipping companies. This study aims to analyze the form of legal liability of shipping companies in COD transactions regarding violations of consumer rights and to identify weaknesses in existing regulations. The research method employed is a normative legal approach using legislative and conceptual frameworks, through a literature review of primary and secondary legal sources. The results indicate that regulations regarding the liability of shipping companies in COD transactions remain unclear and fall within a normative gray area. Shipping companies can no longer be positioned merely as carriers but also as parties involved in the transaction process. Therefore, a proportional liability framework is required using an intermediary liability and joint liability approach. This study emphasizes the importance of legal reform through regulatory harmonization to strengthen consumer protection in digital transactions.